Analyzing 13 Years of Cetacean Strandings: Multiple Stressors to Cetaceans in Taiwanese Waters and Their Implications for Conservation and Future Research - Li, Wen-Ta; Chou, Lien-Siang; Chiou, Hue-Ying; Chen, I-Hua; Yang, Wei-Cheng (Frontiers in Marine Science, 2021)
This study summarizes the postmortem investigations of 73 cetaceans stranded on the coast of Taiwan between 2001 and 2013, including 51 Delphinidae, 17 Kogiidae, 3 Ziphiidae, 1 Physeteridae, and 1 Balaenopteridae. Of these, eight (11%) were categorized into direct human-related strandings, including fisheries interaction (bycatch), vessel collision and other anthropogenic-related pathology. Gastrointestinal foreign bodies were found in eight individuals (11%). Most of the bacteria isolated from stranded dolphins were zoonotic pathogens including extended-spectrum β-lactamases Escherichia coli, which indicates waste pollution from land. Severe parasite infestation was found in 36 of the cases (49%), which suggests that the immune function could be compromised. Thirty-eight cases (52%) were diagnosed with myocardial patchy fibrosis or dilated cardiomyopathy. The evidence shown here indicates that cetaceans around Taiwanese waters may suffer from multiple stressors. This study provides baseline data for the health assessment of cetacean populations in Taiwan, which may ultimately provide recommendations for future cetacean conservation and research throughout the western Pacific.